Current Self-Induction and Potential Well on the Superconductive Rings (Global Journal of Science Frontier Research, 2018)
Work examines new physical phenomenon potential well on the superconductive rings. This Phenomenon indicates that two superconducting the rings of different diameter, in which are frozen the flows, can be found with respect to each other in potential well, when their rapprochement or removal leads to the appearance of restoring force. The distance Between the rings, which determines this pit, corresponds to the minimum of potential energy of the system of the connected rings. This phenomenon can find a practical use for creating the standards of force and highly sensitive instruments for its measurement, such as gravimeters and accelerometers.
Keywords: self-induction; the law of conservation of flow; inductance; superconductivity; current generator; the voltage generator; potential well